Browser based smart home management system - Seow, Patrick Hongyi (2017)
This project extends the focus of a Smart Home Management System by enabling the collection of data from sensors and allows monitoring and automation to Smart Home owners. Through implementation, it replace sensor simulation through proper infrastructure.